On the integration of the energy storage in smart grids: Technologies and applications. Issue 1 (29th April 2019) - Kolokotsa, Dionysia; Kampelis, Nikos; Mavrigiannaki, Angeliki; Gentilozzi, Marco; Paredes, Filippo; Montagnino, Fabio; Venezia, Luca
Abstract: Smart grids are one of the major challenges of the energy sector for both the energy demand and energy supply in smart communities and cities. Grid connected energy storage systems are regarded as promising solutions for providing ancillary services to electricity networks and to play an important role in the development of smart grids. The aim of the present article is to analyze the role of storage systems in the development of smart grids. The article includes an analysis and a list of energy storage systems that are applied in smart grids. Various energy storage systems are examined raging from electrical, electrochemical, thermal, and mechanical systems. Two case studies are presented that show the role of energy storage in effective management of energy demand and supply.